Single-step Au-catalysed synthesis and microstructural characterization of core–shell Ge/In–Te nanowires by MOCVD. Issue 1 (2nd January 2018) - Cecchini, Raimondo; Selmo, Simone; Wiemer, Claudia; Rotunno, Enzo; Lazzarini, Laura; De Luca, Marta; Zardo, Ilaria; Longo, Massimo
ABSTRACT: We report on the self-assembly of core–shell Ge/In–Te nanowires (NWs) on single crystal Si substrates by Metalorganic Chemical Vapour Deposition (MOCVD), coupled to the Vapour–Liquid–Solid (VLS) mechanism, catalysed by Au nanoparticles (NPs). The NWs are formed by a crystalline Ge core and an InTe (II) shell, have diameters down to 15 nm and show <110> oriented growth direction. The role of the MOCVD process parameters and of the NPs size in determining the NWs core–shell microstructure and their alignment was investigated by high-resolution TEM, EDX, XRD and Raman spectroscopy. GRAPHICAL ABSTRACT: IMPACT STATEMENT A novel one-step MOCVD growth procedure, yielding self-assembled, oriented and crystalline core–shell Ge/In–Te nanowires with diameters down to 15 nm, along with their chemical–physical characterization.